Membrane-Bound Configuration and Lipid Perturbing Effects of Hemagglutinin Subunit 2 N-Terminus Investigated by Computer Simulations - Michalski, Michal; Setny, Piotr (Frontiers in Molecular Biosciences, 2022)
Hemagglutinin (HA) mediated fusion of influenza virus envelope with host lipid membrane is a critical step warrantying virus entry to the cell. Despite tremendous advances in structural biology methods, the knowledge concerning the details of HA2 subunit insertion into the target membrane and its subsequent bilayer perturbing effect is still rather limited. Herein, based on a set of molecular dynamics simulations, we investigate the structure and interaction with lipid membrane of the N-terminal HA2 region comprising a trimer of fusion peptides (HAfps) tethered by flexible linkers to a fragment of coiled-coil stem structure. We find that, prior to insertion into the membrane, HAfps within the trimers do not sample space individually but rather associate into a compact hydrophobic aggregate. Once within the membrane, they fold into tight helical hairpins, which remain at the lipid-water interface. However, they can also assume stable, membrane-spanning configurations of significantly increased membrane-perturbing potential. In this latter case, HAfps trimers centre around the well-hydrated transmembrane channel-forming distinct, symmetric assemblies, whose wedge-like shape may play a role in promoting membrane curvature. We also demonstrate that, following HAfps insertion, the coiled-coil stem spontaneously tilts to almost membrane-parallel orientation, reflecting experimentally observed configuration adopted in the course of membrane fusion by complete HA2 units at the rim of membrane contact zones.